2018
DOI: 10.3390/nu10030271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Carob-Pod-Derived Sweetener on Glucose Metabolism

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) have a higher incidence of cardiovascular (CV) events. The ingestion of high-glycemic index (GI) diets, specially sweetened beverage consumption, has been associated with the development of T2DM and CV disease. Objective: We investigated the effects of the intake of a sweetened beverage, obtained from natural carbohydrates containing pinitol (PEB) compared to a sucrose-enriched beverage (SEB) in the context of impaired glucose tolerance (IGT) and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…An important finding is that supplementation with CSAT+ ® decreases the glycemic status and the HOMA-IR, suggesting improved insulin sensitivity. These results are in agreement with previous studies that report increased insulin sensitivity in response to carob treatment both in experimental animals [20] and in humans [18,19,46]. However, other authors have reported that carob consumption in combination with a glucose load increases plasma glucose and serum insulin responses in humans [47].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An important finding is that supplementation with CSAT+ ® decreases the glycemic status and the HOMA-IR, suggesting improved insulin sensitivity. These results are in agreement with previous studies that report increased insulin sensitivity in response to carob treatment both in experimental animals [20] and in humans [18,19,46]. However, other authors have reported that carob consumption in combination with a glucose load increases plasma glucose and serum insulin responses in humans [47].…”
Section: Discussionsupporting
confidence: 93%
“…Among them the fruit of carob tree, (Ceratonia siliqua L.), may be a good candidate since several studies have reported that it exerts beneficial effects improving the glycemic status [18][19][20][21], the lipid profile [22][23][24][25][26], and attenuating the cardiovascular alterations associated with MetS [23,27,28]. Its therapeutic effects are attributed to several bioactive compounds that are present not only in the pulp but also in the pod and the seeds of the carob fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Lambert et al [37] evaluated the effect of having a drink containing natural DP from carob pods compared to a sucrose-enriched drink with a glycaemia profile in healthy volunteers, insulin resistance sufferers and type 2 diabetes. Six weeks of taking of DP-enriched beverage resulted in increased production of proteins involved in the insulin secretion pathway only in people with insulin resistance, not in healthy ones [37]. When assessing carbohydrate metabolism in rats, they proposed a new mechanism to improve this metabolism by administering DP.…”
Section: Cyclitols Insulin Resistance and Diabetesmentioning
confidence: 99%
“…It causes an increase in the amount of complement protein C4A after having a large amount of glucose, correlating with the concentration of C-peptide, which indicates increased secretion of insulin. In addition, C4A protein has a protective effect on β cells of pancreatic islets [37,56].…”
Section: Cyclitols Insulin Resistance and Diabetesmentioning
confidence: 99%
“…The association between obesity and the development of diseases due to the adipose tissue dysfunction is well characterized [16] [17] [18] [19]. However, since the rates of chronic diseases are increasing also in non-obese individuals [20] [21], to clarify the direct effect of nutrients on these illnesses will allow future interventions. The aim of this study was to evaluate the impact of high sugar-fat diet in the development of metabolic-inflammatory disorders in non-obese animals.…”
Section: Introductionmentioning
confidence: 99%